A Novel α-Amylase producing Bacillus drentensis Isolated from Coastal Mud Samples - Prasanth, Manohar; Bozdogan, Bulent; Gothandam, Kodiveri Muthukaliannan; Sivashanmugam, Karthikeyan; Nachimuthu, Ramesh (Asian Journal of Biological and Life Sciences, 2016)
Hydrolytic amylases produced from microorganisms are of high demand due to its larger industrial applications. In this study, α-amylase producing bacteria were isolated from the marine environment and produced enzyme was partially purified. Samples were collected from marine environment and bacterial isolates were screened and identified by 16S rRNA analysis as Bacillus drentensis, Bacillus tequilensis and Bacillus subtilis. Under optimized conditions such as pH, temperature and salt concentrations, higher enzyme activity was observed than normal conditions. In Bacillus drentensis, the enzyme activity of 16.73 U/mL was obtained in pH 5.0 at 40°C with 1% salt concentration. Interestingly, this acidic amylase was stable even at larger salt concentrations. In fermentation period studies, Bacillus drentensis had maximum activity after 48 h incubation, with the cell mass of 2.5 (OD), protein content of 3.1 (mg/mL) and the enzyme activity was 26.33 U/mL. Partial purification by (NH4)2SO4 precipitation at 40% saturation yielded 5.79% enzymes with the specific activity of 46.1 U/mL and the dialyzed extract yielded 14.01% enzyme with 293.1 U/mL of specific activity. SDS-PAGE results revealed that the molecular mass of isolated amylase was approximately 55kDa. Many Bacillus sp. were used to produce amylases but to the best of our knowledge it is the first report on production of α-amylase from Bacillus drentensis with the high specific activity of 293.1 U/mL.
Keywords: Fermentation period; Optimization; Partial purification; Protein concentration